Sinful Income?: Being Muslims and Magic Agents in Madura Island - Indonesia - Haryanto, Bangun Sentosa D (Bina Nusantara University, 2021)
The research was based on a study conducted in four regencies of Madura Island, the mostly Muslim Island in the East Java Province of Indonesia. The research applied a descriptive qualitative method and employed an ethnographic case study consisting of interviews, participant observations, and documentation as data collecting method, analyzed by discourse analysis and textual analysis method. Magic agents, the informants in the research and commonly referred to in Madura as Dhukon were Muslim. In addition, the existence of magic agents on the Island with its dominantly Muslim population was relatively clandestine since practicing/utilizing magic is among the biggest sins in Islamic teachings. Most of these magic agents had no other jobs, and made magic as their primary business commodity to meet their needs and their families. Therefore, their income for their lives relied on their community service activities as supernatural agents. They were likely to perform as Muslim (always wearing Arabic outfits) in daily life and employed some attributes taken from the Qur’an/Hadiths as their ‘tools’; thus, their income was blessed, rather than sinful, income. On average, their income from being Muslim magic agents was mostly higher than that of Regional Minimum Wage (RMW). The researcher argues that being a Muslim magic agent in Madura is a profitable professional job, among other jobs with geographical limitations.